Are catechol-O-methyltransferase gene polymorphisms genetic markers for pain sensitivity after all? – A review and meta-analysis. (May 2023) - Vetterlein, Annabel; Monzel, Merlin; Reuter, Martin
Abstract: The catechol-O-methyltransferase (COMT) gene has arguably been the designated pain sensitivity gene for nearly two decades. However, the literature provides inconsistent evidence. We performed several meta-analyses including k = 31 samples and n = 4631 participants thereby revealing small effects of rs4680 on pain thresholds in fibromyalgia, headache and across chronic pain conditions. Moreover, rs4680 effects were found across pain patients when affected, but not unaffected, body sites were assessed. No effect was detected for any other SNP investigated. Importantly, our results corroborate earlier findings in that we found a small effect of COMT haplotypes on pain sensitivity. Our review and meta-analysis contribute to the understanding of COMT-dependent effects on pain perception, provide insights into research issues and offer future directions. The results support the theory that rs4680 might only impact behavioural measures of pain when descending pain modulatory pathways are sufficiently challenged. After all, COMT polymorphisms are genetic markers of pain sensitivity, albeit with some limitations which are discussed with respect to their implications for research and clinical significance. Highlights: Variation in the COMT gene is associated with pain sensitivity. The effect of val 158 met depends on pain status and body site. val 158 met might affect pain sensitivity when descending inhibition is insufficient. Resting pain sensitivity might be affected by COMT haplotypes. Neurobiological underpinnings of COMT effects on pain perception are illustrated.